The phenomenon of digital paternalism as a factor in the transformation of state youth policy - S. V. Polyakov (Интеллект. Инновации. Инвестиции)
The relevance of this research is determined by the radical transformation of youth communication environments due to digitalization, which reduces the effectiveness of traditional mechanisms of state youth policy and requires conceptualization of new forms of interaction between the state and the younger generation. The aim of the study is to provide a theoretical understanding of the digital paternalism phenomenon as an innovative model of state youth policy and to analyze practical mechanisms of its implementation in modern conditions. The methodological framework includes socio-philosophical analysis, synthesis of neopaternalism concepts, platform capitalism and algorithmic governance, as well as institutional analysis of specific mechanisms for implementing digital paternalism. The research results identify key challenges that digitalization poses to traditional tools of state influence on youth: changing communication channels, transformation of youth community formation principles, declining trust in formal institutions, and changes in cognitive processes of the younger generation. The phenomenon of «digital paternalism» is conceptualized as a mechanism of state interaction with youth through integration into popular digital ecosystems. Its essential characteristics are highlighted: delegation of paternalistic functions to digital platforms, masking of state presence, adaptation to youth digital culture, and creation of an illusion of free choice. Based on the cooperation between government structures and the VKontakte social network, specific mechanisms for implementing the new model are identified: integration of state services into digital platforms, gamification of state initiatives, algorithmic promotion of content, and creation of «trendy» youth movements with state support. The scientific novelty lies in the conceptualization of «digital paternalism» as a qualitatively new stage in the evolution of state youth policy, synthesizing elements of traditional paternalism with the capabilities of digital platforms and algorithmic governance. The practical significance of the research consists in identifying specific mechanisms for implementing digital paternalism that increase youth engagement, reduce negative perceptions of state initiatives, and optimize state resources. Promising directions for further research include studying the potential for implementing artificial intelligence, augmented reality, and blockchain technologies in digital paternalism tools, as well as analyzing the social consequences of transforming models of civic activity and forms of social control. For the full realization of digital paternalism’s potential, it is recommended to ensure transparency of influence mechanisms, address ethical issues, and overcome digital inequality.